Impact of Left Atrial Appendage Morphology on Recurrence in Embolic Stroke of Undetermined Source and Atrial Cardiopathy - Gwak, Dong-Seok; Choi, WooChan; Kim, Yong-Won; Kim, Yong-Sun; Hwang, Yang-Ha (Frontiers in Neurology, 2021)
Background: The left atrial appendage (LAA) is a major source of thrombus and non-chicken wing (CW) LAA morphology is a risk factor for embolic events in atrial fibrillation. However, the association of non-CW morphology with embolic stroke recurrence is unknown in patients with embolic stroke of undetermined source (ESUS) and atrial cardiopathy. Methods: We conducted retrospective analyses using a prospective institutional stroke registry (2013–2017). Patients with ESUS and atrial cardiopathy were enrolled. Atrial cardiopathy was diagnosed if the increased left atrial diameter (>40 mm, men; >38 mm, women), supraventricular tachycardia, or LAA filling defect on computed tomography (CT) was present. Patients admitted > 24 h after onset were excluded. LAA morphology was evaluated using CT and categorized into CW versus non-CW types. The primary outcome was embolic stroke recurrence. Multivariable Cox proportional hazards models were used to examine the independent association between LAA morphology and outcome. Results: Of 157 patients, 81 (51.6%) had CW LAA morphology. The median follow-up was 41.5 (interquartile range 12.3-58.5) months corresponding to 509.8 patient-years. Eighteen participants experienced embolic stroke recurrences (3.80 per 100 patient-years). Non-CW morphology was more associated with embolic stroke recurrence than CW morphology (hazard ratio (HR), 3.17; 95% confidence interval (CI), 1.13–8.91; p = 0.029). After adjusting for CHA2DS2-VASc score and number of potential embolic sources, non-CW morphology showed an independent association with outcome (adjusted HR, 2.90; 95% CI, 1.02–8.23; p = 0.045). Conclusions: The LAA morphology types may help identify the high-risk of embolic stroke recurrence in ESUS with atrial cardiopathy. LAA morphology in atrial cardiopathy may provide clues for developing therapies tailored to specific mechanisms.